Behaviour of reinforced concrete beam under drop-weight impact loading - Wong, Woei. (2013)
Impact loading on reinforced concrete structure has been an important topic for many decades. The study described in this report including assessment of numerical analysis by using FEM software, LS-DYNA on a set of experimental results and efforts on finding the relationship between maximum mid-span displacement, maximum load, and input energy over static shear or bending capacity. Maximum mid-span displacement can be roughly predicted by using the proposed equation method. Asides from that, two empirical formulas for impact resistant design procedure of shear and flexural failure type reinforced concrete beam are derived. By using these equations, the required static bending or shear capacity of an RC beam may be determined by specifying the limit state of maximum mid-span deflections and input impact energy. Recommendation for future research on impact loading is included at the end of the report.